TINJAUAN EKONOMI ISLAM TERHADAP REWARD DAN PUNISHMENT KARYAWAN (STUDI PADA PTPN VII DISTRIK CINTA MANIS KECAMATAN LUBUK KELIAT KABUPATEN OGAN ILIR) - Mistuti Mistuti; Saprida Saprida (Jurnal Ilmiah Mahasiswa Ekonomi Syariah (JIMESHA), 2021)
This research is a field research. This field research conducted observations / observations, qualitative interviews and conducted data validity. The results showed that the rewards in PTPN VII Cinta Manis District were in the form of salaries, bonuses, overtime pay and health benefits. Punishment given is a warning, warning to dismissal. Reward and Punishment at PTPN VII Cinta Manis District has a big influence on employee job loyalty. PTPN VII Cinta Manis District has implemented in accordance with Islamic law.